Actions Toward Containment, Control, and Eradication of Invasive Conehead Termites (Blattodea: Isoptera: Termitidae). Issue 1 (18th May 2021) - Thorne, Barbara L; Alspach, Sue; Tenn, Katherine E; Clark, Marah S
Abstract: Early, strategic IPM actions can eradicate relatively new invasive conehead termite [ Nasutitermes corniger (Motschulsky) (Blattodea: Isoptera: Termitidae)] populations, preventing negative economic and ecological consequences should this pest of agriculture, structures, and natural areas become permanently established and spread. Conspicuous foraging tunnels and above-ground nests are key aspects of N. corniger biology that render colonies vulnerable to discovery and elimination. Because the goal is eradication, the termites must be controlled wherever found—structure, yard, park, overgrown lot, orchard, forest, natural area, etc. Effective IPM methods exist to contain, control, and eradicate invasive nasutes. Removing and safely disposing dead plant material and stored wood helps reduce termite food and harborage, enables liquid insecticides to penetrate soil, and facilitates access for inspections. IPM involves a combination of physical interventions including nest destruction teamed with targeted insecticide applications, followed by diligent monitoring. Fumigation is required only in unusual situations. By killing colonies and reducing overall population size, alate (swarmer) dispersal can be reduced or eliminated, thus substantially slowing—with goal of halting—infested zone expansion. This paper details specific approaches, protocols, and recommendations for detection, treatment, transport prevention, and risk-based monitoring. We present practical suggestions regarding outreach, advocacy, partnerships with stakeholders, and networking with informed professionals. All recommendations stem from the Florida Department of Agriculture and Consumer Services' invasive conehead termite program's best practices and lessons learned experiences during significant mitigation progress, with eradication of two populations of invasive coneheads that spread from a single introduction into Florida as an achievable goal.